In-vitro anti-solar activity of peel of Malus domestica - Supriya Mhamane (Indian Journal of Pharmacy & Drug Studies, 2024)
Hormone production is stimulated by sunlight and it can lead to the synthesis of vitamin D, it also stimulates the reconstruction of cells of the skin. Melanin is the pigment that acts as a natural sunscreen for the skin. Melanin is also stimulated by sunlight. Sunburn, rashes, miliaria, itching, and other skin-related diseases can occur due to the excess harmful sun rays. This study determines the anti-solar property of the UV absorption of the peel of Malus domestica. By using the soxhlet apparatus, the extract was obtained. For extraction of 25gm of the powdered drug, 100ml of solvent i.e. distilled water and methanol in the 2:5 ratio were used. The activity is determined by using UV-visible spectrophotometer in the range of 200–400 nm. The maximum absorbance was determined by conc. 6μg/ml at 205nm, good absorbance shows at conc. 4μg/ml at 207nm and moderate absorbance by conc. 2μg/ml at 207nm.